Sacrocolpopexy for posthysterectomy vaginal vault prolapse: long-term follow-up. Issue 10 (October 2016) - Illiano, Ester; Giannitsas, Konstantinos; Zucchi, Alessandro; Biase, Manuel; Zingaro, Michele; Bini, Vittorio; Costantini, Elisabetta
Abstract Introduction and hypothesis Abdominal sacrocolpopexy (ASC) is considered the gold standard for vaginal vault prolapse (VVP) repair. Our aim was to evaluate the long-term durability of its anatomic and functional results. Methods This was a prospective series of women undergoing ASC for symptomatic VVP stage III or IV according to the Pelvic Organ Prolapse Quantification (POP-Q) system. All patients were followed up every 3 months for the first postoperative year and then annually for anatomical and functional outcomes and complications. Only patients with at least 48 months of follow-up were included in this report. Anatomic success was defined as postoperative prolapse stage 0 or I. Statistical analysis was performed using the nonparametric Mann–WhitneyU test for the analysis of continuous variables and the McNemar and χ2 test for categorical data. Results Sixty-seven women were followed up for a median of 60 months (range 48–144). Anatomical success was 100 % for apical prolapse and 94 and 91 % for anterior and posterior compartments, respectively. There were only four (6 %) and six (9 %) cases of stage II persistence or recurrence for the anterior and posterior compartments, respectively, which did not require reoperation. There was no vault prolapse recurrence. Voiding and storage urinary and sexual symptoms were significantly improved. Anorectal dysfunction symptoms persisted in 40.6 % of patients with these symptoms preoperatively and developed de novo in 22.8 % of patients without them preoperatively. Three mesh exposures were noted. Sixty-three patients (94 %) were extremely or very much improved with sacrocolpopexy according to the Patient Global Impression–Improvement scale. Conclusions Our data confirm the long-term durability of vaginal vault prolapse repair with ASC.